2017
DOI: 10.1016/j.pmrj.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

No Exacerbation of Knee Joint Pain and Effusion Following Preoperative Progressive Resistance Training in Patients Scheduled for Total Knee Arthroplasty: Secondary Analyses From a Randomized Controlled Trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…1 Also of note, patients performed the program without exacerbation of knee joint pain and effusion. 14 In a recent review, five studies were found investigating preoperative interventions including a follow-up of six months or more after total knee arthroplasty. None of the studies showed any longterm effects at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…1 Also of note, patients performed the program without exacerbation of knee joint pain and effusion. 14 In a recent review, five studies were found investigating preoperative interventions including a follow-up of six months or more after total knee arthroplasty. None of the studies showed any longterm effects at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…According to a large body of literature, however, the joint function does not improve after these exercises, and the intensity of training engaged in by the patients varies, with even less attention paid to the degree of improvement in knee strength [ 11 13 ]. It is believed that balance training is as important as muscle training, as patients need to adapt to the altered kinematics caused by the joint prosthesis when getting out of bed or during daily activities [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst heterogeneous preoperative exercise methodologies and levels of evidential quality within meta-analytical reviews, significant improvements (small to moderate effects sizes) have been observed in postoperative function, quadriceps strength, and length of stay in patients undergoing TKA [ 4 ]. Similarly, while preoperative progressive resistance training (PRT) has been shown to be safe and not liable to exacerbate knee joint pain and effusion [ 5 ], the methodological quality of evidence had rendered the effectiveness of PRT before and/or after TKA as inconclusive [ 6 ]. Nevertheless, other reports support the use of short-term (4-week) high-intensity resistance training before TKA [ 7 ] and capable of inducing long-lasting effects on muscle strength [ 8 ], but not necessarily on functional performance [ 8 ] or other patient-reported outcomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%